nifH Gene Sequencing Reveals the Effects of Successive Monoculture on the Soil Diazotrophic Microbial Community in Casuarina equisetifolia Plantations - Zhou, Liuting; Li, Jianjuan; Pokhrel, Ganga Raj; Chen, Jun; Zhao, Yanlin; Bai, Ying; Zhang, Chen; Lin, Wenxiong; Wu, Zeyan; Wu, Chengzhen (Frontiers in Plant Science, 2021)
The growth and productivity of Casuarina equisetifolia decreased distinctly by replant sickness in long-term monoculture regime. In this research, Illumina MiSeq sequencing targeting nifH genes were carried out to assess the variations in the rhizospheric soils diazotrophic community in long-term monoculture rotations. PCA analysis and UPGMA clustering demonstrated distinct differences in diazotrophic community structure among the soil with no C. equisetifolia cultivation (CK), the first rotation plantation (FCP), the second rotation plantation (SCP), and the third rotation plantation (TCP). The taxonomic analysis exhibited that the phyla Proteobacteria was enriched while Verrucomicrobia was decreased in the consecutive monoculture (SCP and TCP). Moreover, the relative abundance of Paraburkholderia, Rhodopseudomonas, Bradyrhizobium, Geobacter, Pseudodesulfovibrio and Frankia increased significantly, while Burkholderia, Rubrivivax, Chlorobaculum declined significantly at the genus level in the consecutive monoculture (SCP and TCP). Results of redundancy analysis (RDA) showed that Burkholderia, Rubrivivax and Chlorobaculum were positively correlated with TN and AN. In conclusion, continuous monoculture of C. equisetifolia could change the structure of diazotrophic microbes in the rhizosphere, resulting in the imbalance of diazotrophic bacteria population, which might be a crucial factor to replanting disease of this cultivated tree species.